Determinants of Knowledge of Women of Reproductive Age Regarding Sexually Transmitted Infections in the Working Area of Kedungrejo Public Health Center - Rahmawati Raharjo; Gufron Wahyudi (Journal for Quality in Public Health, 2025)
Sexually transmitted infections remain global health issues which cause millions morbidity and mortality. Women of reproductive age represent one of the vulnerable groups, as limited knowledge can affect sexual behavior and elevate the risk of transmission.  This study seeks to examine the determinants influencing the knowledge of women of reproductive age regarding sexually transmitted infections. The research employed a cross-sectional design. The population consisted of 115 respondent. The sample consisted of 54 participants. Purposive sampling was used as the sampling technique, and a questionnaire served as the research instrument. Data were analyzed using the Spearman rank test. The findings indicated that age and education did not show a significant association with the level of knowledge (p > 0.000), whereas access to information demonstrated a significant relationship with knowledge about sexually transmitted infections in the working area of Kedungrejo Public Health Center. The knowledge level of women of reproductive age was largely influenced by the availability and accessibility of relevant and up-to-date information. These findings indicate that older age or higher education does not necessarily correspond with increased knowledge about this disease if not supported by adequate information access. Conversely, individuals with good access to information tend to have higher knowledge levels, regardless of their age or education.